2009
DOI: 10.1097/bot.0b013e31818e43dd
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Limb-Threatening Lower Extremity Trauma

Abstract: Patients with severe lower extremity injuries can expect a significant number of complications, most notably wound infection, nonunion, wound necrosis, and osteomyelitis. A large portion of these will require additional inpatient or operative treatment. Patients electing for reconstruction can expect a higher risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(141 citation statements)
references
References 14 publications
5
131
0
5
Order By: Relevance
“…Infection after traumatic and combat-related amputation is relatively common with reported rates as high as 34% [4,9,13,14]. The frequency in our study cohort was similar at 31% and was not found to be different than control subjects without imaging.…”
Section: Discussionsupporting
confidence: 53%
“…Infection after traumatic and combat-related amputation is relatively common with reported rates as high as 34% [4,9,13,14]. The frequency in our study cohort was similar at 31% and was not found to be different than control subjects without imaging.…”
Section: Discussionsupporting
confidence: 53%
“…Consequently, those last three patients had more complications, more operative procedures, and longer hospital LOS than those patients treated with urgent amputation, as is usually the case [14]. Regarding these postoperative complications, the majority of them were related to wound infection, (grade III of the Clavien-Dindo classification), also reported by other studies [5].…”
Section: Limitations Of the Studysupporting
confidence: 55%
“…Despite these efforts, non-union and infection are still common complications with rates of up to 32% and 23%, respectively, reported in civilian severe lower extremity injuries. 1 Similarly, infection is the most common cause of delayed amputation in combat-related open tibial fractures. 2 Bacteria produce biofilm that is protective against microbial agents, 3 and the antibiotic concentrations needed to eliminate these sessile colonies found in biofilms can be more than 500 times those required to kill planktonic bacteria.…”
mentioning
confidence: 99%